2021
DOI: 10.3389/fpubh.2021.621800
|View full text |Cite
|
Sign up to set email alerts
|

Public Perception and Hand Hygiene Behavior During COVID-19 Pandemic in Indonesia

Abstract: Hand hygiene practices are important not only during the corona virus disease 2019 (COVID-19) pandemic, but also critical to prevent the possible spread of other infectious diseases. This study aims to examine the current hand hygiene behaviors during the COVID-19 pandemic, post pandemic behavior intentions, and the relationship between behavior, psychosocial and contextual factors. A cross-sectional online survey was conducted from 28 May to 12 June 2020, with 896 valid responses obtained from Indonesian citi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
68
3
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 32 publications
14
68
3
8
Order By: Relevance
“…In the results of the research, it is stated that providing health protocol facilities such as hand washing facilities for students at pesantren can prevent the transmission. In line with these results, Dwipayanti et al (2021) also stated that washing hands with running water and soap is considered effective in preventing the transmission of COVID-19 with an OR value of 1.77, 1.23-2.54. Thus, the provision of hand washing facilities in the pesantren environment to prevent the transmission of covid 19 is one of the effective efforts to build a clean and healthy lifestyle as an effort to prevent the transmission of covid 19 in the pesantren environment.…”
Section: Discussionsupporting
confidence: 53%
“…In the results of the research, it is stated that providing health protocol facilities such as hand washing facilities for students at pesantren can prevent the transmission. In line with these results, Dwipayanti et al (2021) also stated that washing hands with running water and soap is considered effective in preventing the transmission of COVID-19 with an OR value of 1.77, 1.23-2.54. Thus, the provision of hand washing facilities in the pesantren environment to prevent the transmission of covid 19 is one of the effective efforts to build a clean and healthy lifestyle as an effort to prevent the transmission of covid 19 in the pesantren environment.…”
Section: Discussionsupporting
confidence: 53%
“…The final factor that we identified through the factors analysis was compliance with hygiene measures. Research has already shown that the COVID-19 pandemic affects in a positive way the personal hygiene behaviors such as hand washing (Dwipayanti et al, 2021; Hu et al, 2021; Huang et al, 2021). In general, people have modified their attitudes to confront the risk propensity of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…One can then use the adapted SI forms to inform which hygiene aspects should be tackled, which can then improve the general household hygiene conditions. Some hygiene-related studies have been conducted in Indonesia, for example, on handwashing practices [15][16][17] and general household hygiene conditions [5,13]. There are is also evidence that household hygiene is associated with children's malnutrition in Indonesia [18,19].…”
Section: Of 15mentioning
confidence: 99%